Difficulties implementing continuous improvement initiatives in SMEs - Baier, Robin (2024)
Constant Improvement initiatives offer a significant potential to improve quality and operational efficiency in enterprises but often fail to be implemented effectively to achieve desired results. Since enterprises of different sizes face different problems with implementation, small- to medium-sized companies are looked at in more detail within this thesis. The most common theoretical approaches used for implementation are Total Quality Management, Six Sigma, and Lean Manufacturing. These frameworks have a high failure rate, which enterprises should analyze and minimize before implementation. Specialists in the field of continuous improvement from different organizations have been interviewed, questioning the reasons for failures in their enterprise. The main issues that cause an initiative to fail are divided into Motives and Expectations, Culture and Environment, Management Leadership, Implementation Approach, Training, Project Management, Employee Involvement Levels, and Feedback and Results. Employee involvement level, Motives and Expectations, and Organisational Culture and Environment have been analyzed as the most impactful. The actions to decrease the failure rate depend on the individual enterprise. Although three different categories are mentioned, most failures in small- to medium-sized enterprises can be traced back to the education and knowledge of employees and managers.